Pentingnya Interaksi Dalam Keluarga Dalam Pembentukan Kepribadian Anak - Mus Mulyadi (At-Ta'lim : Media Informasi Pendidikan Islam, 2015)
family interactions have a very strong influence in shaping the child's personality. Keluraga is the first and primary education. Before the children get an education at another institution, the first child to get an education in the family. Relationships within the family is also something that is integral in forming a happy family, all the components of the family should understand and appreciate their obligations and functions. Likewise, in reaching mawaddah warahmah happy family, religious values should form the foundation of the family.